Electrocardiographic signs of cardiac ischemia at rest and during exercise in patients with COPD traveling to 3,100 m: data from a randomized trial of acetazolamide - Christen, Marla; Buergin, Aline; Mademilov, Maamed; Mayer, Laura; Schneider, Simon R.; Lichtblau, Mona; Sooronbaev, Talant M.; Ulrich, Silvia; Bloch, Konrad E.; Furian, Michael (Frontiers in Cardiovascular Medicine, 2025)
IntroductionIn patients with chronic obstructive pulmonary disease (COPD), oxygen delivery to the heart may be impaired during travel at altitude. We assessed electrocardiogram (ECG)-derived signs of cardiac ischemia and the effects of preventive acetazolamide therapy in COPD patients traveling to high altitudes.MethodsPatients with COPD [Global Initiative for Chronic Obstructive Pulmonary Disease (GOLD) grades 2–3] and a predicted forced expiratory volume in 1 s (FEV1) of 66 ± 11% (mean ± SD), aged 57 ± 8 years, and living <1,000 m were included in this analysis of secondary outcomes from a randomized placebo-controlled double-blind trial (www.clinicaltrials.gov, NCT03156231). Exercise electrocardiograms were recorded at the National Center of Internal Medicine and Cardiology, Bishkek (760 m) and on the day of arrival at the Tuja Ashu high-altitude clinic (3,100 m), Kyrgyzstan. Acetazolamide (375 mg/day) or placebo was administered 24 h before the ascent and during the stay at 3,100 m. The incidence of a post-exercise ST elevation (STE) ≥0.3 mm in aVR (J + 80 ms) was the main outcome.ResultsAt 760 m, 3 of 49 (6%) patients randomized to placebo and 3 of 50 (6%) randomized to acetazolamide showed a post-exercise STE. At 3,100 m under placebo, two (4%) new STEs developed and one (2%) disappeared compared to 760 m (P = 0.564, McNemar’s test). At 3,100 m under acetazolamide, one (2%) new STE developed and two (4%) disappeared compared to 760 m (P = 0.564). No treatment effect was detected (P = 0.242, Fisher’s exact test). The mean difference (95% CI) in STE between post-peak exercise between 3,100 m and 760 m was 0.22 mm (0.06 to 0.39) and 0.09 mm (−0.06 to 0.24) under placebo and acetazolamide therapy [treatment effect, −0.13 mm (−0.35 to 0.08, P = 0.230)], respectively.ConclusionsIn lowlanders with moderate to severe COPD ascending to 3,100 m, no ECG-derived signs of cardiac ischemia emerged neither at rest nor post-exercise and this was not modified by preventive acetazolamide therapy.